Acquired Zinc Deficiency Mimicking Acrodermatitis Enteropathica in a Breast-Fed Premature Infant - Giovanna D'Amico; Corinne De Laet; Guillaume Smits; Deborah Salik; Guillaume Deprez; Catheline Vilain; Pascale Perlot; Alfredo Vicinanza (MDPI AG, 2021)
We present a case of a transient acquired zinc deficiency in a breast-fed, 4-month-old-male prematurely born infant, with acrodermatitis enteropathica-like symptoms such as crusted, eroded, erythemato-squamous eruption in periorificial and acral patterns. The laboratory investigations showed low zinc levels in the infant's and the mother's serum and in the mother's milk; genetic analysis did not show any mutation in the SLC39A4 gene, involved in acrodermatitis enteropathica. Acquired zinc deficiency is often found in premature infants because of their increased requirement, the low serum and milk zinc levels in breastfeeding women being also an important risk factor, as in this case. A prompt zinc supplementation is essential for the good prognosis of the disease.